Intracranial Pathologies and Endocrine Results: Single Pediatric Endocrinology Center Experience - Ülkü Gül Şiraz (Genel Tıp Dergisi)
ABSTRACT Intracranial pathologies can affect pituitary hormone levels whether they are primarily related to the pituitary gland or not. In pituitary hormone deficiencies, the size and location of the pituitary gland may be normal, as well as one or more hormone effects may be observed after hypoplasia, partial empty sella, ectopic neurohypophysis, Rathke's cleft cyst, adenomas and other pituitary masses or surgeries. In early puberty, the pituitary dimensions are usually increased, rarely hypoplasia and rathke cleft cyst are seen as MRI findings. Non-pituitary pathologies cause especially early puberty, single or multiple pituitary hormone deficiency. In this study, we aimed to categorize the patients with pituitary/cranial lesions and hormonal pathology and to determine their frequency and distribution in the single pediatric endocrinology clinic for ten years. The data of 485 patients, 186 (38.3%) male, were retrospectively analyzed. Their mean age was 9.3 ± 3.2 years. The incidental pituitary lesion was found in 28 (5.77%) of all cases. There was no hormonal influence in 20 (71.4%) of them. In most of the 454 cases with hormonal disorders, MRI (Magnetic Resonance Imaging) findings were normal in most of the 454 cases with hormonal disorders (71.8%). The most common hormonal pathologies were precocious puberty and isolated Growth Hormone deficiency, 57.9% and 26.4% respectively. Non-pituitary lesions (n=23, 5%) were most frequently accompanied by early puberty (39.1%). The hypothalamus-pituitary axis may be affected by primary lesions in its own region, or it may be seen as a result of other cranial pathologies. Cranial evaluation is also important in addition to pituitary imaging in pituitary hormone disorders.